2014
DOI: 10.1097/igc.0000000000000045
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Leukemia After Chemotherapy and/or Radiotherapy for Gynecologic Neoplasia

Abstract: Long survival time might be expected in patients who show complete response to bone marrow transplantation and/or combination chemotherapy for secondary leukemia. In recent years, we have aggressively used various types of anticancer drugs for the treatment of not only ovarian cancer but also uterine cervical cancer and endometrial cancer. Physicians need to keep in mind the risk of secondary leukemia in the follow-up of long-term survivors after several courses of chemotherapy and radiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…1202 Cisplatin and carboplatin have been widely associated with therapy-related leukemia. 1203,1204 In contrast, for oxaliplatin, an etiological role in secondary hematological diseases has been suggested only in several case reports. 1189 In 2002, two cases of cisplatin-and carboplatin therapy-associated APL, a subtype of AML, have been observed.…”
Section: Secondary Immune-related Cancersmentioning
confidence: 99%
“…1202 Cisplatin and carboplatin have been widely associated with therapy-related leukemia. 1203,1204 In contrast, for oxaliplatin, an etiological role in secondary hematological diseases has been suggested only in several case reports. 1189 In 2002, two cases of cisplatin-and carboplatin therapy-associated APL, a subtype of AML, have been observed.…”
Section: Secondary Immune-related Cancersmentioning
confidence: 99%
“…The side effects of high-dose radiotherapy on normal cells are evident. [15] Chemotherapy has similar side effects and drug resistance possibilities. [16] Hematopoietic stem cell transplantation is one of the most used methods in the treatment of leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…A study on patients with gynecologic malignancies treated in the past 20 years found that there is only 0.38% chance of leukemia development in these patients. However, this percent is not specific to radiotherapy and it involves leukemias developed secondary to chemotherapy, as well [95]. Another study examined patients with invasive tumors of the vulva, cervix, uterus, anus, and rectosigmoid treated with radiotherapy and found that not only the risk of developing leukemia is 72% higher in these patients, but also "the risk of secondary leukemia peaks at 5 to 10 years after primary treatment and remains elevated even 10 to 15 years after initial treatment" [96].…”
Section: Ionizing Radiationmentioning
confidence: 99%